Effects of black rice husk ash on asphalt mixture under aging condition - Putra Jaya, Ramadhansyah; Noor Azlan, A.; Haryati, Yaacob; Mohd Rosli, Hainin; Norhidayah, Abdul Hassan; Mohd Khairul Idham, Mohd Satar; Abdul Rahim, A. H.; Azman Mohamed, M.; Nordiana, Mashros; Ekarizan, S. (IOP Science, 2019)
The scarcities of natural resources and increment in the waste production rates have promoted efforts to investigate the potential incorporation of various by-products in roads construction and maintenance. Various types of waste materials have been investigated, assessed and evaluated for utilization and practiced in the industry. Reusing of waste materials such as black rice husk ash (BRHA) in asphaltic concrete (AC) was considered as one of the proper management of the waste, which ensure economic and environmental benefits. This study was investigated BRHA effects on the properties and performance of asphalt mixture under different aging condition. The BRHA was added in the AC14 mixture in a proportion of 0%, 2%, 4% and 6% by weight of bitumen. The optimum bitumen content was 5% and the bitumen used was 60/70 penetration grades. The asphalt mixture for each fraction was prepared in three different aging conditions i.e. un-aging (UA), short term aging (STA) and long term aging (LTA). The performance of the asphalt mixtures was evaluated by Marshall Stability and resilient modulus. The results indicate that asphalt mixtures consisting of BRHA have exhibited better performance in term of stability and resilient modulus when compared to the conventional asphalt mixtures. The short term and long term aging mixtures considerably produced higher performance than the un-aging mixtures. However, the LTA performed better than of the STA mixtures. Finally, the optimum additional percentage of BRHA was in the range of 4 – 6% since its produce excellent values in most circumstances.